Tinjauan Yuridis terhadap Faktor Penyebab Perceraian di Pengadilan Agama Purwodadi - Mahdaniyal Hasanah Nuriyyatiningrum (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2019)
Married life is very likely to occur a misunderstanding between husband and wife. The situation can sometimes be overcome peacefully, but sometimes the efforts for peace that actually lead to hatred and lead to disputes between the two, even between the two sides of the family. If the marriage continues, then the basic goals of the household will not be achieved. In Islam, divorce is an act that is hated by Allah, but it is permissible. Purwodadi Religious Court is a class IA court. Grobokan Regency occupies the second place in terms of divorce in Central Java, with the number of divorces reaching three thousand. The stereotype of "virgin kasep" from the community towards unmarried eighteen-year-old girls, hopes to escape the snares of poverty make parents hasten to marry their children. With a psychic that is not yet very mature, not a few of the young couples bring their family conflicts to the front of the court, Purwodadi Religious Court. Keywords: Purwodadi Religious Court, factors causing divorce, legislation